2009
DOI: 10.1140/epja/i2009-10734-5
|View full text |Cite
|
Sign up to set email alerts
|

On the chromo-electric permittivity and Debye screening in hot QCD

Abstract: We study the response functions (chromo-electric susceptibilities) for an interacting quark-gluon plasma. The interaction effects have been encoded in the effective fugacities for quasi-partons which are extracted self-consistently from the two equations of state for hot QCD. The first one is the fully perturbative O(g 5 ) EOS and, the second one which is O(g 6 ln(1/g)), incorporates some non-perturbative effects.We find that response function shows large deviations from the ideal behavior. We further determin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 63 publications
6
64
0
Order By: Relevance
“…These fugacities should not be confused with any conservation law (number conservation) and have merely been introduced to encode all the interaction effects at high temperature QCD. Both z g and z q have a very complicated temperature dependence and asymptotically reach to the ideal value unity [48]. The temperature dependence z g and z q fits well to the form given below,…”
Section: Heavy-quark Potentialsupporting
confidence: 59%
See 1 more Smart Citation
“…These fugacities should not be confused with any conservation law (number conservation) and have merely been introduced to encode all the interaction effects at high temperature QCD. Both z g and z q have a very complicated temperature dependence and asymptotically reach to the ideal value unity [48]. The temperature dependence z g and z q fits well to the form given below,…”
Section: Heavy-quark Potentialsupporting
confidence: 59%
“…We analyze the spatial dependence of the heavy quark potential later and compare it against the other known forms of the potentials in the forthcoming sections. To that end, we employ the Debye mass computed from the effective fugacity quasi-particle model (EQPM) [47,48] and compare all the predictions with Debye mass obtained in HTL and Lattice QCD computations. Let us now proceed to discuss the EQPM and Debye mass below.…”
Section: Heavy-quark Potentialmentioning
confidence: 99%
“…al [19,20] have considered two EOS based on pQCD, and developed a self-consistent method to recast them in terms of non-interacting/weakly interacting quasi particles with effective fugacities. Since the method is employed here, we briefly review the work.…”
Section: Hot Qcd Equations Of State and Their Quasiparticle Descrmentioning
confidence: 99%
“…The implications of lattice EOS will be taken up in a subsequent paper. Our study is based on [19,20] where it has been shown how the EOS may be adapted to study the properties of QGP in heavy ion collisions. It is worth mentioning that the above mentioned works have demonstrated the viability of the EOS since they yield reasonable values for the dissociation temperatures for J/Ψ and Υ.…”
mentioning
confidence: 99%
See 1 more Smart Citation